Analysis of the possibilities to achieve the low energy residential buildings standards - Basińska, Małgorzata; Koczyk, Halina (Technological and Economic Development of Economy, 2016)
The article applies the global costs calculation method to the energy assessment of selected solutions for the technical equipping of buildings, dependant on their purpose and function. Representative archetypes, the life span of which were assumed to be 30-years, were used to estimate the performance of the minimum requirements according to the building regulations valid in 2013, current general standards, as well as low energy building and passive house standards. The subjects of the analysis were three residential buildings, for which the variability of the cladding and ventilation needs was assumed. In all analysed cases the application of four systems of energy supply to the building was also assumed. The optimal level of primary energy index value, dependant on the source of heat, was established by means of the global cost method. This level was then compared with the requirements presently valid in Poland. The analysis also allowed for the determination of the growth in investment costs, that must be considered in order to achieve the energy needed for heating and ventilation at the level of 40 kWh/m2/a or 15 kWh/m2/a. The analysis presents a comparison of the subsidized loans for energy-efficient houses offered by the Polish Government.First published online: 23 Nov 2016